KELAYAKAN FILM DOKUMENTER SEBAGAI MEDIA PEMBELAJARAN KONSEP KEANEKARAGAMAN GEN, JENIS, EKOSISTEM DI KELAS X - Nurhuda, Agus; Syamswisna, Syamswisna; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the feasibility of a documentary film as a learning medium on the Sub Material Concept of Genes, Species, and Ecosystems Diversity in the first grade of senior high school. This research was descriptive with sampling in the form of purposive sampling. This research was tested documentary film as a learning medium validated by 3 material experts and 3 media experts as a learning medium on the Sub Material Concept of Genes, Species, and Ecosystems Diversity. The material expert was a lecture of Biology Education FKIP Untan, and a teacher of Biology in senior high school in Mempawah District, while the media expert was a lecturer of Biology FKIP Untan, a lecture of PGRI University Adi Buana Surabaya, and CEO & Founder of MIP (IT & Passion Community). Based on the results of data analysis, an average total validation of 3.8 (valid) which shows documentary film media was appropriate to used. However, documentary media films need to be tested in the learning process in the Sub Material The Concept of Genes, Species, Ecosystems Diversity in the first grade of senior high school.Â Keywords: Learning Medium, Documentary Film, Sub Material of the Concepts of Genes, Species, Ecosystems Diversity